2020
DOI: 10.1002/cssc.202001187
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Lignin Conversion

Abstract: Lignin is the largest source of renewable aromatic compounds, making the recovery of aromatic compounds from this material a significant scientific goal. Recently, many studies have reported on lignin depolymerization and upgrading strategies. Electrochemical approaches are considered to be low cost, reagent free, and environmentally friendly, and can be carried out under mild reaction conditions. In this Review, different electrochemical lignin conversion strategies, including electrooxidation, electroreducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 194 publications
(652 reference statements)
0
104
0
Order By: Relevance
“…11 Among electrochemical approaches, the electro-oxidation of lignin at the anode is the most common one studied. 12 Even if electrocatalytic approaches similar to that adopted in the present study were reported in the literature for other combinations of lignins and working electrodes, [13][14][15] investigations regarding the electrochemical conversion of P1000 lignin, up to now, are absent. Only a few studies are available concerning its chemical valorisation through inorganic catalysts, such as CuMgAlO x or NiMo sulphide, in organic solvents under harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…11 Among electrochemical approaches, the electro-oxidation of lignin at the anode is the most common one studied. 12 Even if electrocatalytic approaches similar to that adopted in the present study were reported in the literature for other combinations of lignins and working electrodes, [13][14][15] investigations regarding the electrochemical conversion of P1000 lignin, up to now, are absent. Only a few studies are available concerning its chemical valorisation through inorganic catalysts, such as CuMgAlO x or NiMo sulphide, in organic solvents under harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 86%
“…One of the main limitations in the scaling-up of electrochemical approaches could be the high cost of metal electrodes or electrode coatings, if for example Pt-based electrodes are involved. 27 Thus, a challenging effort is represented by the development of electrochemical processes based on low-cost electrocatalysts, 12 justifying the choice of graphite and nickel in the present work. In detail, a preliminary investigation of the performances of three different electrode materials (Pt, Ni/NiOOH and graphite) for the P1000 lignin electro-oxidative depolymerisation was performed by cyclic voltammetry adopting different reactions conditions, such as pH 12, 13 and 14, lignin concentration 2 and 20 g L À1 , scan rates 10, 50, 100 and 250 mV s À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Present as the most and second abundant source of biomass, cellulose, and lignin are considered the most attractive proton and carbon source due to their availability and low-cost. Biomass electrolysis of these raw feedstocks, lignin, [271][272][273][274][275] and cellulose [276,277] has therefore also been studied. Similar to methanol and ethanol electrolysis, the primary focus on lignin and cellulose electrolysis is H 2 production with less electricity consumption.…”
Section: Ethanolmentioning
confidence: 99%
“…[58] The same is true at the anode; biomass oxidation hyphenated with cathodic H2O2 production is more feasible if the reactor is built on-site at a bio-refinery, particularly if the H2O2 is used for further oxidations downstream. [59] Many applications of H2O2 do not require concentrated solutions, so cheaper systems that produce working concentrations of H2O2 may be viable on this scale, despite not being able to compete with the AO process in a centralised system. Sequential flow reactors: Delocalised production allows construction of hybrid systems, where H2O2 at the correct concentration is directly supplied to a second process.…”
Section: Latest Developments For H 2 O 2 Electrosynthesismentioning
confidence: 99%